Analisis Faktor Determinan Senjangan Anggaran Pemerintah Republik Indonesia Kementerian Negara Bidang Infrastruktur-Sebuah Studi Eksploratif - Hilda Rossieta; Dri Asmawanti (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2010)
The central role of infrastructure in promoting national economic growth in one hand, yet, on the other hand, low absorption of government budget among infrastructure-related ministries of Indonesia (i.e., Public Works, Transportation, Public Housing and Rural Development), has provided strong motivation to do research in this area. Research framework is developed based on budgeting literature of profit oriented entity as well as current budgeting practice of infrastructure-related ministries in Indonesia. Generally, the study hypothesized that due to bureaucratic type of government organizations, level of budget absorption is negatively associated with degree of uncertainty in both tasks (Dunk and Nouri, 1998) and environment (Kren and Liao, 1988). We use level of efficiency of the standard systems and procedures to guide budget implementation as proxy to the level of uncertainty. Efficient guidance has adequate clarity and comprehensiveness to guide budget execution, so that additional information to reduce uncertainty of task as well as environment is unnecessary. The questioner is developed from the existing systems and procedures that guide each ministry to interact with both internal as well as external parties. The aim of the questioner is to examine the association between the level of uncertainty with level of budget absorption. Respondents of this study are Kuasa Pengguna Anggaran (KPA) in the Directorate General level in the ministries. They are government officials who have the authority to implements the budget. Out of the total 48 KPA in the ministries, we sent 21 questioners or 44% of the total population, and received 18 responses or 85.71 % response rate. After examining validity and reliability of the data, the hypotheses are tested in two ways: (i) nonparametric Kruskal-Wallis test to examine whether the ministries have different level of task as well as environment uncertainty; (ii) nonparametric rank Spearman and Kendall’s tau-b to investigate whether budget absorptions are negatively correlated with the level of uncertainty. The results suggest that the ministries have different level of uncertainty, and also, the level of budget absorption is negatively correlated with the level of uncertainty. Therefore, to increase the level of budget absorption, the budget systems and procedures in the larger ministry such as Ministry of Public Works and Ministry of Transportation with high level of uncertainty should have clearer (i.e., free from ambiguity) and more comprehensive compared to that of the smaller ministries such as Ministry of Public Housing and Ministry of Rural Development.